Efficacy and Safety of Unilateral Biportal Endoscopy Compared With Transforaminal Route Percutaneous Endoscopic Lumbar Decompression in the Treatment of Lumbar Spinal stenosis: Minimum 1-year Follow-up - Sun W; Wang J; Hu Y; Tao J; Yang C (Journal of Pain Research, 2025)
Weixiang Sun, Jie Wang, Yafei Hu, Jinzhuo Tao, Chengwu Yang Pain Department, the Eighth People’s Hospital of Hefei, Hefei, People’s Republic of ChinaCorrespondence: Chengwu Yang, The Eighth People’s Hospital of Hefei, No. 319, Renmin Road, Chaohu City, Hefei City, Anhui Provience, 238000, People’s Republic of China, Tel +86 15256298182, Email yangchengwu0508@126.comObjective: This study compared the efficacy and safety of unilateral biportal endoscopic (UBE) decompression and transforaminal route percutaneous endoscopic lumbar decompression (PELD) for lumbar spinal stenosis (LSS), assessing 1-year clinical outcomes.Methods: A total of 120 patients (64 UBE, 56 PELD) diagnosed with LSS in 2021 were evaluated. Perioperative outcomes included overall operation time, extracanal operative time, intracanal decompression time, incision length, fluoroscopy time, estimated blood loss, preoperative and postoperative day 3 hb levels, length of post-operative hospital stays, total expenses, postoperative complications. Clinical outcomes were measured using visual analog scale (VAS) for back and leg pain, Oswestry disability index (ODI) for physical impairment and the modified MacNab criteria.Results: Results showed no demographic differences between groups. UBE had shorter total operation and intracanal decompression times but longer extracanal operative time than PELD (all P< 0.01). Fluoroscopy time was significantly lower in UBE (P< 0.01). While UBE had longer incisions, greater blood loss, and higher costs, hemoglobin level changes and hospital stays were similar between groups. Postoperatively, UBE resulted in lower VAS-leg pain scores (P< 0.01) and had a higher excellent/good rate (93.75% vs 85.71%, P< 0.05). Moreover, there were 3 patients in PELD group who needed a revision surgery at the same level within postoperative 1-year follow-up due to the unrelieved symptoms.Conclusion: Both techniques were safe, but PELD posed a higher risk of reoperation due to decompression failure. UBE demonstrated advantages in decompression efficiency and clinical outcomes despite longer incision length and greater blood loss.Keywords: unilateral biportal endoscopic, percutaneous endoscopic lumbar discectomy, lumbar spinal stenosis, decompression